2012
DOI: 10.1093/neuonc/nos296
|View full text |Cite
|
Sign up to set email alerts
|

MiR-218 sensitizes glioma cells to apoptosis and inhibits tumorigenicity by regulating ECOP-mediated suppression of NF-κB activity

Abstract: These results suggest that miR-218 sensitizes glioma cells to apoptosis by regulating ECOP-mediated suppression of NF-κB activity, which may provide novel opportunities for glioma therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 30 publications
2
67
0
1
Order By: Relevance
“…Although recent studies indicate that increased miR-218 expression impacts cell viability in nasopharyngeal cancer and GBM cells (20,21), a role for miR-218 in conferring chemoresistance was not known. To test whether miR-218 has such a role, we used a gain-of-function approach by restoring miR-218 expression in GSCs or GBM cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Although recent studies indicate that increased miR-218 expression impacts cell viability in nasopharyngeal cancer and GBM cells (20,21), a role for miR-218 in conferring chemoresistance was not known. To test whether miR-218 has such a role, we used a gain-of-function approach by restoring miR-218 expression in GSCs or GBM cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Two primary glioblastoma cell cultures (GBM1 and GBM2) were derived from glioma patient samples as described previously. 29 The primary glioma cells were cultured as follows: patient biopsies were immediately dissociated by trypsinization and subsequently were cultured in Neurobasal Medium (Invitrogen), with 1× B-27 and 1× GlutaMax I (Invitrogen). All medium was supplemented with 10% FBS (Invitrogen) and 100 U/ml penicillin/streptomycin (Sigma).…”
Section: Methods Cell Lines and Tissue Samplesmentioning
confidence: 99%
“…However, miR-218 expression was lower in A549 cells ( Figure 1A & 1B). Previous studies have indicated that Robo1 is a downstream target of miR-218 [14] and that Ecop is a key functional target of miR-218 [10]. Therefore, Robo1 and Ecop mRNA expression was examined in the same human lung adenocarcinoma cell lines and showed that Robo1 and Ecop was in lower expression in A549 cells and in higher expression in HCC4006 cells ( Figure 1C).…”
Section: Resultsmentioning
confidence: 84%
“…In colon cancer, miR-218 was found to suppress invasion and migration by inhibiting ZEB2 and N-Cadherin [9]. Moreover, miR-218 upregulation was found to inhibit gastric cancer invasion by targeting Gli2 and E-cadherin following Thermo-chemotherapy [10]. These findings suggest that miR-218 is involved in the EMT process by targeting N-Cadherin and E-cadherin, which are the key molecular makers associated with EMT.…”
mentioning
confidence: 82%